Niger’s agrifood system structure and drivers of transformation - Diao, Xinshen; Ellis, Mia; Randriamamonjy, Josee; Thurlow, James; Ulimwengu, John M.; Pauw, Karl (International Food Policy Research Institute, 2023)
Niger is a landlocked country in West Africa, and most of the population relies on subsistence farming. The country faces considerable food security challenges due to a combination of recurring droughts, desertification, population growth, and political instability. The World Food Program estimates that around 1.5 million people in Niger—roughly 6 percent of the population—are food insecure (WFP 2020). Agriculture plays a pivotal role in Niger’s economy, employing more than 80 percent of workers and contributing around 40 percent of GDP. The agricultural system is largely rainfed and productive activities are concentrated in the southern part of the country, particularly in the regions along the Niger River. Only 15 percent of the country’s land is arable, and rainfall is seasonal and highly variable. Millet, sorghum, cowpeas, and groundnuts are the major food crops, while pastoralism is a key component of the agricultural system, particularly in the arid regions in the north of the country. Despite the dominance of agriculture, Niger is a net food importer as agricultural production falls short of domestic food needs (FAO 2018). The government implemented the 3N Initiative (Nigeriens Nourishing Nigeriens) to address the root causes of food insecurity. This initiative aims to promote sustainable agricultural practices, enhance the resilience of farmers to climate change, and improve access to food (IFAD 2020). While rural households produce a significant amount of their own food, the importance of market purchases as a determinant of food security cannot be overstated. Market purchases are the primary food access strategy for Nigeriens for 8–9 months of the year. This highlights the importance not only of primary agricultural production, but also the broader agrifood system (AFS) in ensuring year-round access and availability of nutritious foods. Hence, in this brief we look beyond primary agriculture to understand the performance of Niger’s broader AFS and how it is contributing to growth and transformation in the country.